Fundamental studies of carbon capture using CaO-based materials. Issue 16 (3rd April 2019) - Sun, Hongman; Wang, Jianqiao; Liu, Xiaotong; Shen, Boxiong; Parlett, Christopher M. A.; Adwek, George O.; John Anthony, Edward; Williams, Paul T.; Wu, Chunfei
Abstract : Detailed understanding of the mechanisms of fast stage CaO carbonation was given. Abstract : Detailed understanding of the mechanisms of the fast stage during CaO carbonation is important for the design of novel efficient CaO materials. This work systematically studies the formation of a CaCO3 product layer on the outside surface of CaO grains during the fast reaction stage for carbon capture using two types of CaO adsorbents. The carbonation at 400 °C filled the small pores in the commercial CaO grains and no distinct product layer of CaCO3 was observed. However, a distinct layer of CaCO3 with a thickness around 90 nm was observed on the outside surface of the commercial CaO grains after the carbonation at 600 °C because the internal pores in the CaO grain had been filled and a layer of CaCO3 product was deposited on the outside surface of the CaO grain. For sol–gel CaO, the carbonation reaction is limited by the availability of useful porosity for the growth of CaCO3 product (confinement effect), instead of by the diffusion of ions in the critical layer of the CaCO3 product. No surface product layer was observed. Therefore, fabricating nano-CaO having dimensions less than the critical thickness of the CaCO3 layer (∼90 nm) is of potentially great significance if it can be done cheaply and in bulk.